Fe and Co NMR studies of magnetoelectric Co2 Y-type hexaferrite BSCFAO. (17th January 2018) - Choi, Baeksoon; Kwon, Sangil; Lee, Soonchil; Park, Chang Bae; Shin, Kwang Woo; Kim, Keehoon
Abstract: The Fe 3+ and Co 2+ NMR spectra for Ba0.3 Sr1.7 Co2 (Fe0.96 Al0.04 )12 O22 (BSCFAO) and Ba0.3 Sr1.7 Co2 Fe12 O22 (BSCFO) were obtained in a zero magnetic field at a low temperature. We observed change in the enhancement effect of the NMR signals depending on the setting field, which was varied when applied along the b -axis and then turned off before the measurement was taken. The experimental results indicate that the magnetic structure changes from an alternating longitudinal cone to a transverse cone when the setting field is 250 mT. They also show that the spins of Co 2+ ions together with those of Fe 3+ ions constitute a part of the overall magnetic structure and that the substitution of Al 3+ for Fe 3+ weakens the magnetic anisotropy within the easy plane. From a comparison of the enhancement factors of the Fe 3+ NMR obtained with the RF pulse applied along the a -axis and the c -axis, we found that the magnetic easy plane anisotropy is approximately 16 times greater than the anisotropy within the easy plane. No changes of the NMR spectra were observed under an electric field of 1.2 MV m −1 .